Makna Gambar dan Rupa Allah Serta Konsekuensinya Bagi Manusia - Stimson Hutagalung (Jurnal Koinonia, 2013)
Man is the crown of God's creation which is different from the rest of creation. Created in His image is a testament to how respected man among all the other creations. Humans will be valuable when the image / likeness of God is in him and reflect God’s thoughts and greatness, this is a haven for human judgment standard. Losing one’s self image of God means losing the value of life and not worthwhile anymore. And the power of thought play a vital role in reflecting the image of God made â€‹â€‹man worth.